Linkages of agroecosystems producing farmed seafood on food security, nutritional status and adolescent health in Bangladesh. (21st December 2020) - de Roos, Baukje; Roos, Nanna; Ara, Gulshan; Ahmed, Tahmeed; Mamun, Abdullah‐Al; Sneddon, Alan A.; Murray, Francis; Grieve, Eleanor; Little, David C.
Abstract: This narrative review aims to provide an interdisciplinary perspective on actors that link global aquatic food production systems with fish consumption and nutritional status, with a special focus on adolescent girls in Bangladesh. The writing of this narrative perspective was undertaken within the framework of the Aquatic Food for Health and Nutrition (AQN) project that aimed to develop a metric for assessing the impacts on nutrition and health of agroecosystems producing farmed seafood. Previous studies evaluating links between agricultural ecosystems, aquaculture, food security and human health have systemically ignored the importance of diet and nutrition. Such studies have also ignored the importance of local communities, cultural norms and household composition and behaviours to identify vulnerable groups such as adolescent girls. This narrative review presents our current understanding of the relationships between aquaculture, fish production and consumption patterns, food security, optimal nutrition and health. It also highlights the importance of research into aquaculture food systems, linking aquatic food production systems with nutritional status, health and socioeconomic prosperity, which would help to develop more integrated and relevant food policies.